DEVELOPMENT OF WHITEBOARD ANIMATION MEDIA TO IMPROVE STUDENT'S LEARNING INDEPENDENCE - Eka Zahriana; Nuraini Nuraini; Abdul Kadir (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2022)
Mathematics education has always received special attention in the world of education. This is because mathematics is one of the supporting factors for assessing learning achievement in a national exam (UN). However, the reality shows that in the learning process, the teaching materials used have not trained students in making discoveries and students have not been independent in the learning process. This study aims to produce a product in the form of videoscribe-based whiteboard animation media and to test the feasibility and effectiveness of videoscribe-based whiteboard animation media to increase student learning independence made using the Sparkol Videoscribe application on a 4GB DDR4 Memory Laptop. This research uses a descriptive qualitative approach with the type of Research and Development (RD). This development process uses a 4D (four-D) research model with 4 stages of development, namely (1) Define (2) Design (3) Develop (4) Disseminate, with the research subject being one material expert and one media expert. Data collection techniques using interviews and questionnaires (questionnaires), data analysis techniques used in the form of data analysis techniques Likert Scale. The result of this research is a whiteboard animation media to increase students' learning independence which is suitable to be used as a learning medium at SMPN 1 Nisam. The feasibility of the media produced by both material experts and media experts obtained the results that the media developed was valid and feasible to use.Keywords: Media Whiteboard Animation, Videoscribe, Independent Learning